Overview of Baker's Yeast as a Biocatalyst - Kankarne, Satish Sureshrao; Shinde, Nirmala Vikram (Current Catalysis, 2024)
Biocatalysis is an approach to green chemistry. A crucial step in the synthesis of organic compounds is the reduction of aldehydes and ketones to secondary alcohols. The use of a biocatalyst, such as enzymes or entire cells, has not affected this process. It offers great selectivity, high specificity, and an environmentally friendly approach to synthesis. Dried baker's yeast mediates the conversion of optically active alcohols from aromatic aldehydes and ketones. This work highlights applications of Baker's yeast in synthesizing pharmaceutical intermediates and chiral building blocks, demonstrating its practical relevance. Sustainable technology is based on the ideas and measurements of sustainable development and green for good enantioselectivity across several organic solvents.
Keywords: organic synthesis